Archives et recherches statistiques - Naud, Gérard (Gazette des archives, 1974)

Archives et télévision : l'expérience de Brest - Foucher, Roger (Gazette des archives, 1971)

L'accès du public aux documents d'archives - Mahieu, Bernard; Bernard, Gildas (Gazette des archives, 1975)

L'enseignement de l'archivistique en Amérique latine - Tanodi, Aurelio (Revue de l'Unesco pour la science de l'information, la bilbiothèconomie et l'archivistique, 1979)

L'exploitation systématique des dossiers individuels des internés au camp de Gurs (Pyrénées-Atlantiques) - Laharie, Claude (Gazette des archives, 1976)

L'exploitation systématique du fonds de la Maîtrise particulière des Eaux et Forêts de Béarn au XVIIIe siècle (Recherches sur l'occupation du sol dans les pays de l'Adour) - Desplat, Christian (Gazette des archives, 1973)

L'exposition « Coligny » aux Archives nationales. Quelques réflexions de visiteurs - Putfin, Guy; Babelon, Jean-Pierre (Gazette des archives, 1973)

L'exposition "Louis-Philippe, l'homme et le roi" - Putfin, Guy; Salmon, Jacques; Babelon, Jean-Pierre (Gazette des archives, 1976)

La conservation et la consultabilité des archives contemporaines au Grand-duché de Luxembourg - Spang, Paul (Archives et bibliothèques de Belgique (ABB), 1979)

La consultation - Roy, Jacqueline (Archives, 1979)

La documentation audiovisuelle : cinémathèque/vidéothèque - Institut national de l'audiovisuel (Ina) (Institut national de l'audiovisuel (INA), 1978)

La loi du 17 juillet 1978 (France) : de la liberté d'accès aux documents administratifs - Gorgeon-Demartres, A. (La Gazette des archives, 1979)

La loi du 3 janvier 1979 et la communication des documents - Charpy, Jacques (Gazette des archives, 1979)
The Archive Law of 3 January 1979 and access to archives. Access to information is nowadays considered to be a fundamental right of the citizen. The author explains the former state of regulations in this field before explaining the new one. Access to administrative documents will need the elaboration of technical solutions and a co-ordination between Archives and administrations from which the documents come. Dérogations to the general rules of access will have to be organised, as well as reading-room regulations and delivery of copies.

La loi du 3 janvier 1979 (France) et la communication des documents - Charpy, Jacques (La Gazette des archives, 1979)

Le montage audio-visuel « La Bible et l'épée » à l'exposition « Coligny » - Putfin, Guy; Babelon, Jean-Pierre (Gazette des archives, 1973)

Le nouvel état des fonds du Bundesarchiv de Coblence : réflexions sur l'accès du public aux archives - Ducrot, Ariane (Gazette des archives, 1978)
After the recent publication of the new Guide to the contents of the Bundesarchiv in Koblenz, some reflexions about the policy of Archives for the publicity of their contents : regulations as to access, finding aids, help given to researchers, etc.

Le public des Archives de la Sarthe, 1967-1978 : agir ou subir ? - Naud, Gérard (Gazette des archives, 1979)
The users of the Archives of the Sarthe, 1967-1978 : to act, or to suffer ? A statistical study of the composition and evolution of the users of a French Department's Record Office. Statistics have served to establish a few facts, but they could not play the role which the author had fancied in the orientation of the activities of his service. Their main interest is to moderate or correct subjective appreciations on immediate data.

Les Archives et les activités culturelles - Taillemite, Étienne (Synthèse des débats des réunions régionales de l'Association des archivistes français en 1974, 1974)

Les relations des Archives avec le grand public - Babelon, Jean-Pierre (Gazette des archives, 1972)

Une curieuse utilisation des documents d'archives ! - Quétin, Michel (Gazette des archives, 1972)